The pattern of brain oxygen response induced by intravenous fentanyl limits the time window of therapeutic efficacy of naloxone. (15th June 2023) - Curay, Carlos M.; Irwin, Matthew R.; Kiyatkin, Eugene A.
Abstract: Opioids induce respiratory depression resulting in coma or even death during overdose. Naloxone, an opioid antagonist, is the gold standard reversal agent for opioid intoxication, but this treatment is often less successful for fentanyl. While low dosing is thought to be a factor limiting naloxone's efficacy, the timing between fentanyl exposure and initiation of naloxone treatment may be another important factor. Here, we used oxygen sensors coupled with amperometry to examine the pattern of oxygen responses in the brain and periphery induced by intravenous fentanyl in freely moving rats. At both doses (20 and 60 μg/kg), fentanyl induced a biphasic brain oxygen response—a rapid, strong, and relatively transient decrease (8–12 min) followed by a weaker and prolonged increase. In contrast, fentanyl induced stronger and more prolonged monophasic oxygen decreases in the periphery. When administered before fentanyl, intravenous naloxone (0.2 mg/kg) fully blocked the hypoxic effects of moderate-dose fentanyl in both the brain and periphery. However, when injected 10 min after fentanyl, when most of hypoxia had already ceased, naloxone had minimal effect on central and peripheral oxygen levels, but at a higher dose, it strongly attenuated hypoxic effects in the periphery with only a transient brain oxygen increase associated with behavioral awakening. Therefore, due to the rapid, strong but transient nature of fentanyl-induced brain hypoxia, the time window when naloxone can attenuate this effect is relatively short. This timing limitation is critical, making naloxone most effective when used quickly and less effective when used during the post-hypoxic comatose state after brain hypoxia has already ceased and harm for neural cells already done. Highlights: Electrochemistry was used to examine fentanyl-induced changes in brain oxygen. Iv fentanyl induced rapid, strong but relatively short (<8–12 min) brain hypoxia. Iv naloxone injected before fentanyl fully blocked brain oxygen responses. Naloxone used 10 min post-fentanyl had minimal effects on brain oxygen changes. In periphery, fentanyl induced prolonged hypoxia, which was attenuated by naloxone.